Virtual and mixed reality-- New trends international conference, Virtual and Mixed Reality 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, Proceedings. Part I - International Conference on Virtual and Mixed Reality Orlando, Fla.) 2011; Shumaker, Randall; SpringerLink (Online service). (Berlin New York Springer, 2011)
The two-volume set LNCS 6773-6774 constitutes the refereed proceedings of the International Conference on Virtual and Mixed Reality 2011, held as Part of HCI International 2011, in Orlando, FL, USA, in July 2011, jointly with 10 other conferences addressing the latest research and development efforts and highlighting the human aspects of design and use of computing systems. The 43 revised papers included in the first volume were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: augmented reality applications; virtual and immersive environments; novel interaction devices and techniques in VR; human physiology and behavior in VR environments.
International conference proceedings.
Electronic reproduction.
Keywords: Virtual reality -- Congresses; Electronic books